Entomopathogenic Nematodes: A review - Nada Sabeeh Othman; Asmaa Mansour Al-Hakeem; Huda Hazim Al-Taee (Zien Journals, 2022)
The aim of study is data collection about entomopathogenic nematodes and mutual bacteria and their effect on insects caused harmful to plants and the mechanism they cause in killing insects.
Keywords: Entomopathogenic; Heterorhabditis; Steinernema